Transformasi Media Pembelajaran Digital melalui Pemanfaatan Artificial Intelligence untuk Meningkatkan Kompetensi Guru Sosiologi pada Komunitas Guru Sosiologi Gowa - St. Haniah; Nur Riswandy Marsuki; Sitti Asnaeni; Abidah R. Delu; Ratnah Rahman (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Digital transformation in education requires teachers to possess the competence to utilize Artificial Intelligence (AI) in developing innovative learning media. This community service initiative aimed to enhance the competence of Sociology teachers in leveraging AI to support the transformation of digital learning media. The activity was conducted on Saturday, June 27, 2026, in partnership with the Gowa Sociology Teachers' Community, involving 35 participants. The methods employed included community education, training, and the dissemination of science and technology through lectures, demonstrations, hands-on practice, and guided instruction on the use of ChatGPT, Canva AI, Gamma AI, Quizizz AI, and Google Gemini. The results demonstrated that participants were able to develop various digital learning media, such as instructional materials, interactive presentations, visual aids, and AI-based assessments. This initiative strengthened the teachers' digital competencies and encouraged the creative, effective, and responsible use of AI in Sociology instruction.